Towards a Gender Sensitive Teacher Education: a research in Basic Education - Queirós, Telma Maria Gonçalves (2018)
In the context of current social and educational policies, guided by values of citizenship and equal opportunities, it is crucial that teacher education develops social and ethics dimensions in the future professionals. However, inequalities persist in society, like those related to gender. Education and teacher education are promising fields for changing. The Bologna process has put new challenges and created new opportunities to higher education in order to rethink Initial Teacher Education (ITE). Simultaneously, demands for improvement issues about equity and gender in curriculum of teacher’s education have strengthened.This research represents an additional step in the interpretation of gender and its relation to ITE, once gender in teacher education is a relatively under research area. The lack of knowledge regarding an analysis of gender issues in ITE is, therefore, one of the starting points for this research. Elementary school teachers need to understand gender policies and how they impact on their teaching before they can begin to challenge these.Within this context, the main purposes of this study are: (i) to analyze whether gender issues are addressed in the study plans and modules of the Master Degree Programs (MDP) on 1st Cycle of Basic Education (CBE) in all public polytechnic institutes of Portugal; to know the student teachers perceptions about gender about gender sensitive teaching practices.To meet the main goals of this investigation, a qualitative methodological approach will be used, applying in-depth interviews and document analysis. The sample will consist of: i) the plans and modules of MDP of 1st CBE in all public portuguese polytechnic institutes; ii) the student teachers of one public polytechnic institute selected. Data will be analyzed independently by two researchers and their findings will be compared at a later stage. The procedures for analysis and discussion of the results will be followed by other researchers in order to promote a comparison with our beliefs, values and biases. It is our understanding that the results of this investigation will be important to make aware of the ways gender issues interfere in teacher education, revealing the absence of this issues in basic education programs. On the other hand enables the awareness and reflection about a set of meanings and practices in student teaching in elementary school regarding gender issues. Moreover, it also expected that the results will provide some insights that suggest crucial recommendations to the administrators of the courses of MDP regarding the importance of include gender issues in initial teacher training programs for an improved educational environment in elementary school classes.